Operational assessment of the geoecological state of the Krivoy Rog area using remote sensing data - Titarenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
An approach to the operational assessment of the geoecological state of Krivoy Rog based on the remote sensing data is offered. Changes of terrain elevations and the vegetation cover using remote sensing methods and geoinformation technologies are studied. The independent classification features of the studied area using the geospatial analysis of time-different multispectral satellite imagery and radar data are analyzed.